Hubungan Tingkat Kecerdasan Spiritual Dan Kecerdasan Sosial Terhadap Self Efficacy Pada Siswa Kelas XI di MAN 4 Madiun - Ullin Nuril Farida; Badrus (Intelektual: Jurnal Pendidikan dan Studi Keislaman, 2019)
Learning concentration becomes an important requirement in learning activities. This should be the concern of all educators, if they want to achieve their educational goals. In this context, this research with the theme of spiritual intelligence, social intelligence and self efficacy in solving a problem is very important to be implemented.This research is a quantitative research. The population in this study all students of class XI in Senior High School 4 Madiun, amounting to 136 students, because more than 100, the study used a sample of 34 students. The data collection techniques use documentation and questionnaires. The analysis technique uses multiple linear analysis, the coefficient of determination, which is preceded by an assumption test of analysis, namely the validity test, reliability test, normality, linearity test and hypothesis test.This study wants to see, [1] the relationship of spiritual intelligence to self efficacy, [2} the relationship of social intelligence to self efficacy, and [3] the relationship of spiritual intelligence and social intelligence to self efficacy in class XI Senior High School 4 Madiun. The results of this study indicate that: [1] significant influence between spiritual intelligence on self efficacy, denger regression coefficient of spiritual intelligence variable is 0.694 [2] significant influence of social intelligence on self efficacy, with regression coefficient of social intelligence variable of 0.543 and [3] significant influence spiritual intelligence and social intelligence together towards self efficacy.